2021
DOI: 10.1177/02692163211059343
|View full text |Cite
|
Sign up to set email alerts
|

Using advance and emergency care plans during transfer decisions: A grounded theory interview study with care home staff

Abstract: Background: Advance care planning has been identified as one of few modifiable factors that could reduce hospital transfers from care homes. Several types of documents may be used by patients and clinicians to record these plans. However, little is known about how plans are perceived and used by care home staff at the time of deterioration. Aim: To describe care home staff experiences and perceptions of using written plans during in-the-moment decision-making about potential resident hospital transfers. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…Similarly in our data, GPs talked about the value of involving care staff in different aspects of the conversation because of their more detailed knowledge of, and relationship with, residents and their families. Similar to our findings, care home staff have previously been found to view the completion of ACP as primarily the responsibility of the resident’s GP, though they were also positive about being actively involved in supporting conversations and viewed plans as reflecting residents’ wishes and the views of healthcare professionals and family members [ 15 ]. Previous research has highlighted the importance of ACPs being reviewed regularly [ 15 ] and the value of early and ongoing conversations in providing opportunities to discuss wishes for the future [ 22 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similarly in our data, GPs talked about the value of involving care staff in different aspects of the conversation because of their more detailed knowledge of, and relationship with, residents and their families. Similar to our findings, care home staff have previously been found to view the completion of ACP as primarily the responsibility of the resident’s GP, though they were also positive about being actively involved in supporting conversations and viewed plans as reflecting residents’ wishes and the views of healthcare professionals and family members [ 15 ]. Previous research has highlighted the importance of ACPs being reviewed regularly [ 15 ] and the value of early and ongoing conversations in providing opportunities to discuss wishes for the future [ 22 ].…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have demonstrated the value of ACP in terms of decreasing inappropriate hospitalisation rates and higher levels of concordance between patient/family wishes and medical treatments undertaken [ 12 15 ]. This, coupled with the high levels of acceptability for ReSPECT in care homes identified in our study, suggests that ReSPECT has the potential to have a positive impact on emergency treatment and end-of-life care pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented were derived from a study exploring care home staff decision-making about residents who potentially require a hospital transfer. Previously published work, which draws solely on the interview data, described care home staff perceptions and experiences of using written advance and emergency care plans during in-the-moment decision-making about potential resident hospital transfers [ 32 ]. The current paper draws on both phases of data collection to develop a conceptual model of care home staff decision-making (presented in Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis and model development reported here was undertaken as part of a study to develop an in-depth understanding of staff decision-making when deciding whether or not to transfer a resident to a hospital [ 31 ]. We have already published interview findings from this research specifically on the role of advance and emergency healthcare plans during in-the-moment decision-making about potential resident transfers [ 32 ]. In this current paper we broaden the focus to the decision-making processes that precede a hospital transfer and the complex weighing-up of risks that are undertaken.…”
Section: Introductionmentioning
confidence: 99%